2021
DOI: 10.1172/jci150867
|View full text |Cite
|
Sign up to set email alerts
|

Mild COVID-19 despite autoantibodies against type I IFNs in autoimmune polyendocrine syndrome type 1

Abstract: Autoantibodies to interferon (IFN)-α and IFN-ω (type-I-IFNs) were recently reported as causative for severe COVID-19 in the general population. Autoantibodies against IFN-α and IFN-ω are present in almost all patients with Autoimmune-Polyendocrine-Syndrome Type 1 (APS-1) caused by biallelic deleterious or heterozygous dominant mutations in AIRE. We therefore hypothesized that autoantibodies against type-I-IFNs also predispose patients with APS-1 to severe COVID-19. We prospectively studied six patients with AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 20 publications
2
81
0
Order By: Relevance
“…These data suggest that the presence of neutralizing autoantibodies to type-I IFNs and the inflammation-prone lung tissue of APECED patients may heighten their risk for life-threatening COVID-19 complications ( 11 , 84 , 101 ). Of interest, another recent study reported four APECED patients who developed mild COVID-19 infection despite the presence of neutralizing autoantibodies to type-I IFNs, consistent with a model of incomplete clinical penetrance ( 102 ). These patients were <26-year-old, female, and did not have pre-existing autoimmune pneumonitis ( 102 ).…”
Section: Pathogenesis Of Aire Deficiencymentioning
confidence: 68%
See 1 more Smart Citation
“…These data suggest that the presence of neutralizing autoantibodies to type-I IFNs and the inflammation-prone lung tissue of APECED patients may heighten their risk for life-threatening COVID-19 complications ( 11 , 84 , 101 ). Of interest, another recent study reported four APECED patients who developed mild COVID-19 infection despite the presence of neutralizing autoantibodies to type-I IFNs, consistent with a model of incomplete clinical penetrance ( 102 ). These patients were <26-year-old, female, and did not have pre-existing autoimmune pneumonitis ( 102 ).…”
Section: Pathogenesis Of Aire Deficiencymentioning
confidence: 68%
“…Of interest, another recent study reported four APECED patients who developed mild COVID-19 infection despite the presence of neutralizing autoantibodies to type-I IFNs, consistent with a model of incomplete clinical penetrance ( 102 ). These patients were <26-year-old, female, and did not have pre-existing autoimmune pneumonitis ( 102 ). Collectively, these reports indicate that APECED patients, particularly adults and/or those with underlying pneumonitis, can be at risk for severe COVID-19.…”
Section: Pathogenesis Of Aire Deficiencymentioning
confidence: 68%
“…Another recent study reported that 4 APECED patients with neutralizing autoantibodies to type-I IFNs developed mild COVID-19; all 4 patients were females with ages younger than 26 years old, without underlying autoimmune pneumonitis (29). Currently, therapies for COVID-19 in patients with rare genetic disorders are extrapolated from randomized controlled trials (RCTs) in the general population and published experience is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In a large study of 22 APS-1 patients, most ( n = 19, 86%) suffered from severe or critical COVID-19 and four patients died; the others had mild or asymptomatic infections, possibly due to prior or early medical interventions ( Bastard et al, 2021c ). Another group recently described four younger APS-1 patients with neutralizing auto-Abs, who developed only mild or moderate COVID-19 ( Meisel et al, 2021 ). Overall, patients with APS-1, particularly those over the age of 25 yr, are at very high risk of developing severe or critical COVID-19 pneumonia.…”
Section: Neutralizing Auto-abs Against Type I Ifns Underlie Severe Or...mentioning
confidence: 99%